Generasi Z dan Isu Kemanusiaan: Perspektif Global dalam Menggadapi Bencana Alam dan Konflik Bersenjata - Meta Marsetya Azzahra; M Purwoadi Santoso (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study analyzes the role and perspective of Generation Z in addressing global humanitarian issues, particularly related to natural disasters and armed conflicts. In the context of increasingly complex global dynamics, Generation Z exhibits unique characteristics, such as high digital connectivity and significant social sensitivity. The findings indicate that this generation not only responds to humanitarian crises through digital initiatives but also acts as active agents of change. However, they face challenges, including limited access to resources and skepticism from previous generations. This research recommends further collaboration between Generation Z and various stakeholders, as well as enhanced education and training to strengthen their response to humanitarian crises.